2007
DOI: 10.1111/j.1469-8986.2007.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

The time course of building discourse coherence in schizophrenia: An ERP investigation

Abstract: Impairments in the buildup and use of context may lead to disorders of thought and language in schizophrenia. To test this hypothesis, event-related potentials (ERPs) were measured while patients and healthy controls read sentences that were highly causally related, intermediately related, or unrelated to preceding contexts. Although patients were slower than controls, both groups used the discourse context similarly as evidenced by similar reaction time patterns across conditions. Neurally however, different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 76 publications
(89 reference statements)
11
90
1
Order By: Relevance
“…The preponderance of previous studies using these SOAs has suggested less than normal activation of concepts related to the prime in patients with schizophrenia as reflected in larger than normal N400 amplitudes in response to related targets and smaller than normal N400 semantic priming effects (Condray et al 2003;Condray et al 2010;Ditman and Kuperberg 2007;Kiang et al 2011;Kiang et al 2008;Kostova et al 2005;Kostova et al 2003;Laurent et al 2010;Mathalon et al 2010;Ohta et al 1999;Salisbury 2010;Salisbury 2008;Strandburg et al 1997). In contrast, our results-namely, smaller than normal N400 amplitudes to both related and unrelated targets-were consistent with heightened activation within semantic memory of concepts both related and unrelated to the prime.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The preponderance of previous studies using these SOAs has suggested less than normal activation of concepts related to the prime in patients with schizophrenia as reflected in larger than normal N400 amplitudes in response to related targets and smaller than normal N400 semantic priming effects (Condray et al 2003;Condray et al 2010;Ditman and Kuperberg 2007;Kiang et al 2011;Kiang et al 2008;Kostova et al 2005;Kostova et al 2003;Laurent et al 2010;Mathalon et al 2010;Ohta et al 1999;Salisbury 2010;Salisbury 2008;Strandburg et al 1997). In contrast, our results-namely, smaller than normal N400 amplitudes to both related and unrelated targets-were consistent with heightened activation within semantic memory of concepts both related and unrelated to the prime.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, a few other schizophrenia studies have found smaller than normal N400 amplitudes to contextually related targets and increased N400 relatedness priming effects (Kreher et al 2009;Kreher et al 2008;Mathalon et al 2002;Salisbury 2008). However, these latter data appear to be specific to short primetarget stimulus-onset asynchronies (SOAs; i.e., the time interval between the onsets of the two stimuli) of <300 ms, weakly related targets, and patients with disorganized speech and are thus suggestive of rapid automatic priming of weakly associated concepts in this subset of patients (Ditman and Kuperberg 2007;Kreher et al 2009;Salisbury 2008). On balance, however, N400 studies of schizophrenia patients provide evidence of a general reduction in semantic priming, at least at SOAs of approximately 300 ms or greater, during which more controlled or strategic cognitive processing is normally thought to occur.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In patients with schizophrenia, a large number of studies have provided evidence of larger than normal N400s in response to target stimuli that are related to preceding context, and/or smaller than normal N400 semantic priming effects (Bobes et al, 1996;Strandburg et al, 1997;Ohta et al, 1999;Condray et al, 2003;Kostova et al, 2003;Iakimova et al, 2005;Kostova et al, 2005;Ditman & Kuperberg, 2007;Kiang et al, 2008;Salisbury, 2008;Guerra et al, 2009;Condray et al, 2010;Mathalon et al, 2010;Kiang et al, 2011;Kiang et al, 2012;Kiang et al, 2014). These results suggest that persons with schizophrenia are impaired in using meaningful contextual stimuli to activate related concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this pattern appears specific to short prime-target stimulus-onset asynchronies (SOAs) of less than approximately 300 ms, and patients with disorganized speech; and is thus thought to reflect an excess of rapid spread of activation in the semantic network of disorganized patients in particular (Ditman and Kuperberg, 2007;Salisbury, 2008;Kreher et al, 2009). Thus, this "hyperpriming" is not necessarily mutually exclusive with the presence of semantic priming deficits over longer time intervals in schizophrenia patients more generally.…”
Section: Introductionmentioning
confidence: 99%